Worker's satisfaction and intention toward working from home-foreign non-EU citizens vs. national workers' approach: Case study of central european countries (visegrád group (v4)) - Pierre Alassaf; Basem Munir El-assaf; Zsigmond Gábor Szalay (Administrative Sciences, 2023)
The COVID-19 lockdown has brought about many sudden changes in the social and work environment, causing organizations and businesses to change work conditions to adapt to the new situation which has affected millions of workers who shifted to telework. The teleworkers' variations in gender, age, residency situation, status as national or foreign employees, and many other aspects create differences in their response toward the telework experience. This study attempts to fill the literature gap concerning the differentiation in response between national and foreign employees' satisfaction with the working from home experience and their future intention to work from home, with a case study of the Visegrád Group as an example from Central European countries. The study found that 84.4% of teleworkers were satisfied with working from home, but no significant difference was found between national and foreign teleworkers in their satisfaction with the telework experience; this satisfaction mainly derives from allocating the gained time to social-personal activities. A surprising result presented by this research is that, in spite of the fact that foreign non-EU-citizen workers were satisfied with the teleworking experience, they do not tend to work from home due to fears of losing their jobs and residence permits, whereas national teleworkers have the intention to work from home if given the opportunity. Another important addition of this study is the development of a new scale specifically for measuring employee satisfaction with working from home instead of using traditional job satisfaction scales.
Keywords: 350; CE countries; employee intention; job satisfaction; telework; V4 countries; willingness to work remotely; work from home; working from home satisfaction scale